Squat and overhead press strength and their correlation to performance in the 2019 crossfit open workouts - Capulong, Willord T. 1994- (College of Human Kinetics, University of the Philippines Diliman, 2019)
CrossFit has continued its popularity in the fitness sphere in recent years, with over 13,000 affiliate gyms across 120 countries and 400,000+ participants in the annual CrossFit Open. Along with the new set of qualification rules where 2 national CrossFit Open champions for each country (1 male and 1 female) earn spots to the CrossFit Games, more countries today are welcome to participate in the sport of CrossFit. The study aims to determine the relationship between 2019 CrossFit Open performance and strength variables measured in the Squat and the Overhead Press (OHP) exercises. Ten males (10) and ten females (10) age 18-34 participated in the study. The participants' back squat and Overhead Press One-Rep Maxes (IRM) were measured before performing all the 2019 CrossFit Open Workouts as prescribed every week which lasted for 5 weeks before the overall rank was determined. Correlation analyses between the squat strength and OHP strength variables to each of the 5 Open Workout scores (using Pearson correlation coefficient) and their Overall Ranks (using Spearman rank-order correlation) were conducted. The results indicate that the 2019 Open workout categorized as 'Task Priority' showed positive significant correlations (Squat Strength). Furthermore, there was sufficient evidence to conclude that there are significant relationships between Squat strength scores in most of the 2019 Open Workouts (19.3 to 19.5). However, the findings are still insufficient to support those strength variables in the Squat and OHP relate to a significant increase in overall Crossfit Open rank after 5 weeks (weak negative correlation of -0.285 and -0.175, respectively).